PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. KEBUN PANTAI RAJA BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Hasanah, Ulfia; ', Suhardi; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Social responsibility and the environment that have been enjoined in Law Number 40 Year 2007 regarding Limited Liability Company, which aims at realizing sustainable economic development to improve the quality of life and the environment that are beneficial to the local community and society in general and the Company itself in the context of relations Company harmonious, balanced, and in accordance with the environment, values, norms, and local culture. As for the purpose of writing this essay, namely: First, to determine the mechanism of implementation of Corporate Social Responsibility at PT. Raja Beach Gardens in the village of Tanjung Pauh Hilir Subdistrict Singngingi. Second, to determine the measures to be implemented by PT. Palm Beach King in the implementation of Corporate Social Responsibility can improve the economy of the local community.This research is a sociological research that want to see the unity between law and society with the gap between das sollen and das sein. This research was conducted in the village of Tanjung Pauh Subdistrict Singngingi Hilir Regency Kuantan Singngingi, while the sample population is the whole party related to the issues examined in this study, the data source used, primary data and secondary data, data collection techniques in this study conducted through interviews, literature studies and questionnaires.The conclusion of this study is, for the First Implementation of corporate social responsibility on a PT. Raja Beach Gardens in the village of Tanjung Pauh Hilir Subdistrict Singingi not refer to the Riau Provincial Regulation No. 6 of 2012 on Corporate Social Responsibility in the province of Riau. The implementation of the CSR that has been done by PT Raja Beach Gardens is by giving some money to the village authorities and improvement of roads to roads that have been damaged. However, in the implementation of CSR is still found deficiencies in various fields, namely the field of development, community economic development, education, the environment and social welfare. Both efforts should be undertaken by PT. Palm Beach King in the implementation of Corporate Social Responsibility which can improve the economy of the local communities that provide training to people who do not have jobs, guidance to UMKM, to form farmer groups and provide scholarships to students and student achievementKeywords: Social Responsibility Company - Community Economic Locale - Limited Liability Company